University Students’ English Language Improvements through a Content-Based Course - Erica Gómez Flórez; Jhon Jaime Jiménez Díaz; Sergio Alonso Lopera (HOW, 2011)
Content-Based Instruction (CBI) may result in improved proficiency in language skills due to the meaningful combination of subject matter and foreign language as a means of communication. This paper shows how university students improved their level of English by means of a content methodology as they attended a course called Topics in Molecular Microbiology. The course was a collaborative enterprise between the School of Microbiology and the School of Languages at a public university. The methodology used was a case study. Five instruments and the MELICET test were used and analyzed in order to check students’ language gains. The findings support that seven undergraduate students improved their speaking and listening skills. Finally, this study offers two implications: Universities should offer more CBI courses; language teachers and content teachers should work collaboratively.